Analysis of Introverted Students’ Writing Skills Using Linguistic Intelligence Tests - Raissa Khumaira; Eva Astuti Mulyani; Hendri Marhadi (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study was motivated by the tendency to assess linguistic intelligence with a greater emphasis on verbal activity, so that the potential of students with introverted tendencies cannot be fully seen and is likely to be misunderstood. This study aims to obtain an overview of the writing skills of students with introverted tendencies in grade V of SDN 191 Pekanbaru using a linguistic intelligence test. The research method used is descriptive quantitative with a sample of 7 students who have introverted tendencies at SDN 191 Pekanbaru. Data collection was conducted through a personality questionnaire using the Eysenck Personality Inventory (EPI) scale and a writing skills test measured through five indicators, namely content relevance to the title, use of standard Indonesian spelling and grammar, choice of vocabulary, sentence structure, and neatness of writing. The results showed that the linguistic intelligence of students in terms of writing skills was in the fairly high category with an average score of 75.71. These findings prove that students with introverted tendencies have good linguistic intelligence, especially in terms of writing skills. This confirms that linguistic intelligence cannot be assessed solely based on speaking activity. Therefore, it can be said that the linguistic intelligence of students with introverted tendencies has developed quite well through writing activities as a form of language expression.